Agricultural Health Economics: A Systematic Review Of Health Risks, Productivity, and Rural Household Welfare - Sitompul, thomson (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
This study aims to analyze the relationship between the health conditions of farmers and their implications on the productivity and economic welfare of agricultural households through a literature review approach. This study examines various empirical studies from several countries, namely Indonesia, Thailand, Cambodia, Australia, Germany, China, the Netherlands, Japan, and Brazil, which discusses the impact of pesticide exposure, work injuries, health shocks, health literacy, and socio-economic factors on the economic performance of the agricultural sector. The results of the review show that health problems, both in the form of diseases due to chemical exposure and work accidents, consistently negatively impact the number of effective working days, labor productivity, and farmers' household incomes. In addition, health literacy, education level, access to health services, and the use of personal protective equipment have proven to be important determinants in reducing health risks and economic losses. Cross-country studies show that even in countries with advanced health systems, such as the Netherlands, Germany, Japan, and Australia, health shocks still affect agricultural productivity. Meanwhile, in developing countries such as Indonesia, Thailand, Cambodia, and Brazil, limited access to health services and low occupational safety education magnify the economic impact of health problems. This research confirms that health is an integral part of human capital in the function of agricultural production and needs to be considered in sustainable agricultural development policies.